Stomach Contens of Mystus nigriceps Valenciannes from the Tarai River, Tarai Bangun Village, Tambang Sub-Regency, Kampar Regency, Riau Province - Rekana Choli Br S Colia; Deni Efizon; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMystus nigriceps is a type of freshwater fish that live in the Tarai river. This research aims to understand the stomach content of the fish. Samplings were conducted in the Tarai River, 5 times, once/2 weeks for a three months period. The fish was captured using nets, scoop nets and bamboo trap. The number of fish caught  was 102, but 4 fishes had empty stomach and they cannot be analyzed. The method used was gravimetric. Stomach content of the fish was analyzed as a basic to calculate the Preponderance index (PI). Results shown that the main food of the fish from Tarai River was insect (PI 71.93%), the complementary food was fish (PI 6.06%) and unidentified materials (PI 13.46%) and the additional food was plant (PI 1.36%), crustaseans (1.51%) and domestic waste (1.57%). Based on data obtained, Mystus nigriceps can be categorized as carnivore. Keyword: Catfish, Feeding Habit, Index of Preponderance, Carnivore fish